Removal of arsenic from liquid copper blister during remelting in an induction vacuum furnace - Albert Smalcerz; Leszek Blacha; Jerzy Łabaj; Bartosz Chmiela (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
The use of reduced pressure in the processes of smelting and refining metal alloys allows  not only the removal of gasses dissolved in the alloy, but also the removal of impurities characterized by high vapour pressure. When the smelting process is carried out in vacuum induction furnaces, the intensification of the discussed processes is achieved by intensive mixing of the bath as well as an enhancement in the mass exchange surface (liquid metal surface) due to the formation of a meniscus, which is a derivative of the electromagnetic field applied to the liquid metal. The presented study presents the results of blister copper refining in terms of removing arsenic from it. The tests were carried out in an induction vacuum furnace in the temperature range of 1423-1523 K, at an operating pressure from 8 to 1333 Pa. The values of the overall mass transfer coefficient kAs determined on the basis of experimental data ranged from 9.99×10-7 to 1.65×10-5 ms-1. Elimination of arsenic was largely controlled by mass transfer in the gas phase. Only for the pressure of 8 Pa the kinetic analysis indicated that the rate of arsenic evaporation was controlled by the combination of both liquid and gas phase mass transfer.